KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA RUMAH SAKIT UMUM SOEDARSO PONTIANAK - Sulistiawan, Aprianto; Marlenywati, Marlenywati; Ridha, Abduh (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2014)
Chronic kidney disease is a chronic disease need dialysis therapy treatment . The prevalence of CRF in the General Hospital Soedarso increased 7.64 % in 2012 to 22.9 % when compared to 2011, and January-March 2013 amounted to 12.86 % . Chronic kidney disease affects the patient's quality of life already begun with circumstances resigned because of illness must rely on tools hemodialysis . The purpose of the study to determine what factors are associated with quality of life of patients with chronic renal failure Hemodialysis diruang dr Soedarso. Design studies using cross-sectional design . Population of 329 people , minimum sample taken in this study was 149 respondents . Sampling with non- probability sampling technique that uses sampling incidental. The results showed that there is a significant correlation with quality of life in patients with chronic kidney crows that age (p value = 0,025 , PR = 1,487) , gender (p value = 0,005 , PR = 1,601), the frequency of hemodialysis (p value = 0,000 , PR = 1,855), stage chronic renal failure (p value = 0,043, PR =1,403), coping skills (p value = 0,041, PR = 1,405) to kidney failure, and as for variables which are unrelated family support ( p value = 0,105,). Advice need for better coping ability of any patient with chronic renal failure that would affect the incidence of stress that will affect the quality of life .